Probing faculty perspectives and experiences for framework development of an online university- industry-government collaboration platform - Ramirez, Hazel Joyce M.; de Guzman, Renen Szilardo C.; Villar, Ricard B.; de Luna, Marie Josephine M.; Sabido, Mia Kaye T.; Sison, Luis G.; Monterola, Sheryl Lyn C. (2024)
University-industry-government (UIG) collaboration nurtures the innovation ecosystem that sustains competitiveness and drives national economic growth. In the Philippines, however, there is limited collaboration between the UIG, thus resulting in untapped opportunities. An integrated web-based collaboration platform for researcher profiles, tools, and resources in Philippine higher education institutions (HEIs) would help promote and strengthen UIG collaboration. In this light, this study conducted a baseline assessment to gain insights into the faculty members’ perceived motivations, current contexts, and challenges of UIG collaborations. These insights guided the development of a framework that would inform the development of an online collaboration platform. The survey was participated in by 111 faculty members from a university system. Analysis showed that respondents had a wide range of experiences in their collaboration, wherein there was an overall satisfaction rating of 3.99 on their collaboration. Findings revealed that building connections or networks and professional development were the main drivers for faculty members to engage in collaboration. On the other hand, communication- and coordination-related issues were among the top collaboration challenges. Also identified as concerns were the differences in perspectives and the low commitment levels of some collaborators. The respondents expressed the necessity for an integrated platform that can facilitate collaboration activities, including opportunity-matching aligned with their professional experience and research interests. Better project management and streamlining of administrative processes were also cited to further enhance the collaboration experience. These findings underscore the necessity for improvement in strategic planning, resource allocation, enhanced faculty support, and opportunity-matching aligned with faculty expertise that can facilitate more effective collaboration among stakeholders. This research has essential implications for the improvement of the collaboration and similarly could provide important inputs and salient features for the development of a UIG collaboration platform.
Keywords: Education (Higher); Academic-industrial collaboration; Faculty